Analisis Pengalaman Pengguna Aplikasi Transportasi Umum dengan Metode User Experience Questionnaire - Oktavia, Alvina Shanaz; Lestari, Rani Wahyu; Nugroho, Aryo (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2024)
Public transportation is very often used in developed countries, including Indonesia and one of the transportation that is currently rife in East Java is transportation using buses. This study aims to conduct a comparison between two public transportation applications in Surabaya and its surroundings, namely Gobis Suroboyo Bus and Transjatim applications using the User Experience Questionnaire (UEQ) method. This UEQ method is used to measure the quality of an application and is assessed from user experience based on six scales which are grouped into 3 quality aspects. In the course of this research, a questionnaire survey was conducted to users of the Gobis Suroboyo Bus and Transjatim applications and distributed to 97 respondents in the Gobis Suroboyo Bus application and 96 respondents in the Transjatim application. The results of the analysis of user experience on the Gobis Suroboyo Bus application and Transjatim application show that respondents have a positive impression. It can be seen in the mean value of 26 items that show positive evaluation (has a mean value> 0.8). Then on the results of the comparison of the two applications with UEQ from 6 scales assessed, the Transjatim application is superior on all scales compared to the Gobis Suroboyo Bus application with slightly different value results.